Bottle-brush-shaped heterostructures of NiO–ZnO nanowires: growth study and sensing properties. (20th October 2017) - Baratto, C; Kumar, R; Comini, E; Ferroni, M; Campanini, M
Abstract: We present here heterostructured ZnO – NiO nanowires (NWs), constituted by a core of single crystalline ZnO NWs, covered by poly-crystalline NiO nanorods (NRs). The bottle-brush shape was investigated by scanning electron microscopy and transmission electron microscope, confirming that a columnar growth of NiO occurred over the ZnO core, with a preferred orientation of NiO over ZnO NWs. The heterostructured devices are proposed for gas sensing application. Bare ZnO NWs and heterostructured sensors with two different thicknesses of NiO poly-crystalline NRs were analysed for acetone, ethanol, NO2 and H2 detection. All sensors maintained n-type sensing mechanism, with improved sensing performance for lower thickness of NiO, due to high catalytic activity of NiO. The sensing dynamic is also strongly modified by the presence of heterojunction of NiO/ZnO, with a reduction of response and recovery times towards ethanol and acetone at 400 °C.